ENGLISH LEARNING DIFFICULTIES FACED by SANTRI in ISLAMIC BOARDING SCHOOL: AN ANALYSIS - Umar Umar (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
Abstract: This case study intended to analyze the higher graders’ English learning difficulties of the Islamic Education Guidance and Counselling study program and Islamic Education Management. This study mainly focused on finding students’ difficulties in mastering English competency. It was conducted in Sekolah Tinggi Ilmu Tarbiyah (STIT) Buntet Pesantren Cirebon by involving 40 students who are also as Santri and a lecturer as the subjects or the researcher. The researcher used both classical and individual approaches in gathering both qualitative and quantitative data. The procedures used context, input, process, and product/CIPP-Evaluations Model for its benefit to increase teaching quality. The data was analyzed by using McDonough & McDonough Model, i.e.: (1) exploration on both students’ learning processes and the results; (2) analyzing the results of exploration through questionnaire, interviewing with students; (3) conducting peer-debriefing, i.e. interviewing with other lecturers related to, the methods, syllabus content, whether they have matched with the students’ needs. The findings showed that students’ English learning difficulties for: (1) Their sense of being-forced; (2) Low mastery on the basic concept/intakes; (3) Less-endorsement from their environment; (4) Forget factor; (5) Having less-chance to practice. In reference with the findings, it was suggested that teachers and institution should facilitate and give high motivation for their students’ English learning process.